2019
DOI: 10.1186/s13756-019-0490-x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis due to glycopeptide resistant Enterococcus faecium from colonized maternal gut- rare case evidence

Abstract: BackgroundVancomycin-resistant enterococcal infections in the neonatal ICU are growing global problems. We report a case of neonatal septicemia by multidrug-resistant vancomycin-resistant Enterococcus faecium (VRE), the source of infection being the mother’s gut.Case presentationA newborn male child admitted to the neonatal intensive care unit (NICU) was diagnosed to have mild meconium aspiration syndrome, early onset neonatal septicemia, and bacteremia by multidrug and vancomycin-resistant Enterococcus faeciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Moreover, the relative abundance of Enterococcus was positively correlated with neonate neutrophil and WBC counts, which are indicators of infection and inflammation (Huang et al, 2018). This result supports the association between Enterococcus and neonatal infection, which has been reported in previous studies (Wang et al, 2014;Subramanya et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the relative abundance of Enterococcus was positively correlated with neonate neutrophil and WBC counts, which are indicators of infection and inflammation (Huang et al, 2018). This result supports the association between Enterococcus and neonatal infection, which has been reported in previous studies (Wang et al, 2014;Subramanya et al, 2019).…”
Section: Discussionsupporting
confidence: 86%
“…Empirical therapy of early-onset neonatal sepsis is based on the combination of ampicillin plus an aminoglycoside, whereas that of late-onset neonatal sepsis is based on the combination of vancomycin plus an aminoglycoside ( Shane et al, 2017 ). Additionally, linezolid could represent a valuable alternative in neonatal ICUs with high prevalence of vancomycin-resistant Enterococci ( Subramanya et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical therapy of early-onset neonatal sepsis is based on the combination of ampicillin plus an aminoglycoside, whereas that of late-onset neonatal sepsis is based on the combination of vancomycin plus an aminoglycoside (Shane et al, 2017). Additionally, linezolid could represent a valuable alternative in neonatal ICUs with high prevalence of vancomycin-resistant Enterococci (Subramanya et al, 2019). Antimicrobial TDM may be very helpful in this challenging scenario, considering that in the newborns the relationship between drug dose and exposure is quite unpredictable, especially in the pre-terms, due to the abrupt developmental physiological changes that occur in this age period (Pauwels and Allegaert, 2016;De Rose et al, 2020).…”
Section: Neonatal Sepsismentioning
confidence: 99%
“…It is known that enterococci is one of the first few bacteria that colonize primarily in the neonatal digestive system via originating from the mother's vaginal or gastrointestinal flora. [14] Subramanya et al [15] reported one early onset septicemia case by vankomisin resistant Enterococcus faecium. They found the same VRE strain from blood samples of the neonate and stool speciemens of the mother at the same time and indicated that maternal gut colonization caused neonatal sepsis.…”
Section: Discussionmentioning
confidence: 99%